Pengembangan Google Sites untuk Meningkatkan Literasi dan Hasil Belajar Mapel Administrasi Sistem Jaringan SMK Negeri 1 Kwanyar Bangkalan - Ainul Yakin; Nuril Huda; Sucipto (Pusat Riset dan Inovasi Nasional, 2024)
The rapid utilization of the internet as a 21st-century learning resource makes digital literacy an essential competency that students need to possess, in addition to critical thinking skills. Therefore, it is necessary to develop technology-based learning media to support the improvement of both skills. This study aims to develop Google Sites-based learning media to enhance students' digital literacy abilities and learning outcomes. This research is a development study (R&D) referring to the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were teachers and 11th-grade students of the Computer and Network Engineering (TKJ) program at SMKN 1 Kwanyar. The developed learning media demonstrated results categorized as highly feasible, practical, and effective for use in the learning process of the Network System Administration subject. The effectiveness assessment results showed that student learning activity was classified as very active, and there was a significant improvement in critical thinking skills, indicated by an average N-Gain score of 0.75, which falls into the moderately effective category. Validation from experts showed that this learning media obtained a score of 90% from media expert validators, 93% from material expert validators, and 95% from educator assessments, all of which were in the